ANALYSIS OF MODERN DEVELOPMENTAL TRENDS OF POSITIONING STRATEGIES OF LEADING UNIVERSITIES IN THE INTERNATIONAL INFORMATION SPACE (Comparative Professional Pedagogy, 2021)
The scientific research is devoted to a relevant issue, namely the current trends in the development of positioning strategies of leading universities in the international information space. University positioning strategies in the international information space are aimed at the leadership at the market of educational services. University activities should be noticed and evoke a «positive image». To achieve this goal PR-managers develop sets of special measures, forms and tools in order to make a positive impression on the minds of the target audience. The author of the scientific research has firstly analyzed the essence of the concept «trends» in general and then in education in particular. In the conditions of competitive processes in the field of higher education, demographic crisis, fewer number of applicants, introduction of corporate governance principles in state universities, a wider range of researches, administration and PR-managers of higher education institutions should apply modern forms and methods of positioning their own activity and educational products. On the grounds of the comparative analysis conducted in the previous researches on positioning strategies of the leading Western European and Ukrainian universities in the international information space the following trends of this process have been identified: positioning the leading (research and corporatized) university in the international information space; focusing the university positioning strategy on the target market segment; positioning cross-border cooperation and internationalization of the university in the context of increasing international competition between individual universities; promoting the positioned brand as a guarantee of the quality of university education in the international information space; changing the ratio of traditional and modern types of advertising.
Keywords: trends; development; positioning strategies; top universities; international information space